Pembelajaran Online terhadap Hasil Belajar pada Masa Pandemi Covid 19 - Dewi Shinta Wulandari Lubis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
We have experienced Covid 19 for 2 years, what we call the covid 19 pandemic, the policy to maintain distance to reduce the spread of the covid 19 virus has changed the learning process from a face-to-face model to an online learning model. The lecture learning process is carried out online with the obligation to maintain and pay attention to the quality of learning so that maximum learning outcomes are achieved, as well as paying attention to the learning motivation of the students themselves. The purpose of this study was to determine and describe the effect of learning motivation and learning quality on student learning outcomes during the pandemic. Where the respondents of this study were students of the Sukma College of Management Sciences (STIM) who were active until 2020. This study used a quantitative descriptive method. This study concluded that there was a partial and simultaneous influence between learning motivation and learning quality on student learning outcomes during the pandemic